Bioactive compounds from Ploiarium alternifolium (Theaceae) and Calophyllum mucigerum (Guttiferae) - Ng, Kim Nee (2001)
Chemical and cytotoxic studies were carried out on two plant species, Caiophyllum mucigerum (Guttiferae) and Ploiarium alternifolium (Theaceae). The chemical investigations covered anthraquinones, triterpenes, xanthone and coumarins. These compounds were isolated using common chromatographic techniques and HPLC and identified using spectroscopic methods including 2-D NMR, GCMS, MS, IR andUV. Ploiarium alternifolium provided emodin, ploiariquinone A, 1,8-dihydroxy-3- methyl-6-methoxy-anthraquinone, 3 β-benzoyloxyolean-ll-en-13β,28-olide and euxanmodin C. Emodin and 1, 8-dihydroxy-3-metbyl-6-methoxy-antbraquinone have not been reported from Ploairium aiternifolium. Calophyllum mucigerum gave the common steroidal triterpenes friedelin and stigmasterol, a prenylated xanthone cudraxanthone C and two new coumarins mucigerin I and mucigerin II. The crude n-hexane, ethyl acetate and ethanol stem bark extracts of both plants were screened for their larvicidal activity against the larvae of Aedes aegypti. The crude n-hexane, ethyl acetate and ethanol extracts for both of the plants were susceptible to the larvae of Aedes aegypti with LC₅₀ values of 95.0 µg/ml, 129.4 µg/ml and 131.6 µg/ml, respectively for Ploiarium alternifolium whereas 87.9 µg/ml, 138.5 µg/ml and 147.4 µg/ml, respectively for Calophyllum mucigerum. Larvicidal activity on the pure compound, emodin gave an LCso value of 2.79 µg/ml. The cytotoxicity, antibacterial and antifungal activities test were also carried out on the three crude extracts of both plants and also on the pure compounds. Cytotoxicities were determined by performing the microtitration assay. All the crude extracts were weakly cytotoxic towards the CEM-SS cell line except hexane extracts from C. mucigerum and P. alternifolium which gave moderate activity with IC₅₀ = 16.2 µg/ml and lC₅₀ = 19.2 µg/ml, respectively. The pure compound euxanmodin C was the most sensitive against the cell line with IC₅₀ = 5.9 µg/ml. The antimicrobial activity was tested using the modified disc diffusion method. The crude extracts from both plants also showed different antimicrobial activity against the growth of four bacteria; Bacillus subtiUs mutant, Bacillus subtilis wild type, Staphyloccus aures and Pseudomonas aeruginosa. However, these crude extracts were weakly active against the bacteria with less than 10 mm diameter inhibition zone.